Study on Adsorption Kinetics of Methylene Blue by Modified Sago Frond Waste - Seniman Gempur Tirani; Sunardi Sunardi (Program Studi Kimia, Universitas Lambung Mangkurat, 2022)
The modified sago frond waste (PSM) using the Fast Microwave-Assisted Acid method, which has several characteristic changes, was tested to determine its adsorption ability to a cationic textile dye. PSM samples as adsorbents have variations in the modification of oxalic acid addition at 0; 1,5; 3,0 and 4,5% (w/v) were used for the adsorption of Methylene Blue (MB) dye on several parameters. This study was conducted to determine the adsorption kinetics through the effect of the ratio of the adsorbent and the contact time and the acid variation of the adsorbent as additional variables. Optimum MB absorption was obtained at a ratio of 0,6 g/L and a contact time of 120 minutes. The data results were analyzed using four general kinetic models: pseudo-first-order, pseudo-second-order, intra-particle diffusion, and Elovich equation. Adsorption followed the pseudo-second-order reaction rate with a coefficient of determination (R2) 0.9996-0.9999 in all variations of PSM. The theoretical adsorption capacity was 25.58 to 27.32 mg/g, and the effect of increasing acid on PSM increased the adsorption and absorption capacity of MB. Keywords: sago frond waste, adsorption, kinetic models, methylene blue.